Pengaruh Sistem Pembayaran Nontunai dan Penerimaan Pajak terhadap Pertumbuhan Ekonomi - Ramadanti, Annisa Putri; Kistanti, Nurjannah Rahayu (UI Scholars Hub, 2024)
Technology has shifted the payment system from cash to cashless method. It turns out that has an impact on the fiscal sector and economic growth. This study aims to examine and analyze the effect of cashless payment systems on economic growth through tax revenue as a variable intervening in 2013-2022. Partial Least Squares-Structural Equation Modeling (PLS-SEM) is used as an analysis method. The result of this study shows that cashless payment systems proxied by electronic money, debit/ATM cards, and credit cards have an impact on economic growth through tax revenue as an intervening variable, while internet banking does not. In outline, the use of cashless payment media has the potential to increase in Indonesia. Therefore, policymakers should collaborate with various parties, such as banks and society, to boost the use of cashless payment instruments as a medium of tax payment and increase economic growth.